(untitled) (Journal of Partial Differential Equations, 2018)
In this paper, the Dirichlet problem in the vertical half-band for the degenerated elliptic equation with singular coefficient and spectral parameter is investigated. Using the Hankel transformation and the method of separation of variables, the solution of the Dirichlet problem is presented in the explicit form.